Analysis of The Influences of Biodiesel On Performance and Emissions of a Diesel Engine - Siddeg, Abu Bakar; Adam, Umar; Jaat, Norrizam; Khalid, Amir; Sapit, Azwan; Mohd, Sofian; Abd. Jalal, Mzahar (Journal of Automotive Powertrain and Transportation Technology, 2023)
Biodiesel remains an alternative fuel of interest for use in diesel engines. A common characteristic of biodiesel relative to petroleum diesel, is a lowered heating value (or energy content of the fuel). This review paper discusses the characteristics of biodiesel that has a great influence on the performance and emission of diesel engine. A lower heating value of the fuel, assuming all other parameters are equal would result in decreased engine torque. Since engine torque is often user-demanded, the lower heating value of the fuel generally translates into increased brake specific fuel consumption. The biodiesel from edible oils is non-toxic, biodegradable and renewable alternate fuel that can be used as a substitute for diesel in diesel engines. There is some indication that the use of biodiesel fuel can degrade diesel engine oil performance to such an extent that shortening of oil drain intervals is required. Oil, which is fuel-diluted with biodiesel, which is also known to contain unsaturated hydrocarbon bonds would be expected to be more prone to oxidation. Besides, the use of biodiesel leads to the substantial reduction in PM, HC and CO emissions accompanying with the imperceptible power loss, the increase in fuel consumption and the increase in NOx emission on conventional diesel engines with no or fewer modification. Plus, it favors to reduce carbon deposit and wear of the key engine parts. Therefore, the blends of biodiesel, with small content in place of petroleum diesel, can help in controlling air pollution and easing the pressure on scarce resources without significantly sacrificing engine power and economy. However, many further researches on optimization and modification of engine, low temperature performances of engine, new instrumentation, methodology for measurements and etc., should be performed when petroleum diesel is substituted completely by biodiesel. In this study, reports about biodiesel engine performances and emissions, published by highly rated journals in scientific indexes were cited preferentially since the year 2000. From these reports, the effect of biodiesel on engine power, economy, durability, emissions including regulated and non-regulated emissions and the corresponding effect factors are surveyed and analyzed in detail.